Independent study approach and the educational needs of gifted learners (2021)
The concept of giftedness is diverse because it connotes different things in certain contexts. Cognitive giftedness as intellectual prowess enables the learners to demonstrate a high level of thinking, reasoning and retrieval of facts and figures. Therefore, cognitively gifted individuals learn faster and better than their age groups. The implication of this accomplishment among the precocious students is that they have educational needs which the general school programmes and services do not meet. This is essentially contributing to the dropout rate among the gifted in our schools. Therefore, as an approach to meeting these needs, independent study is advocated in this paper. The approach is a planned research process that develops cognitive and creative skills in gifted learners. It is a stage- by-stage endeavour that caters for the learning styles, preferences and abilities of the 'students. The impact of the approach on gifted learners is beyond the frontiers of the classroom-or school environment as it fosters the students’ social performance. At this juncture, the teacher, as the programme facilitator, guides and motivates the students throughout the exploratory pursuit of interest. As a matter of recommendation, professionals in the field of gifted education are enjoined to make a case for independent study (learning) for the gifted The cognitive and creative expression of the students will be given room for if the approach is incorporated. It is also recommended that curriculum planners, designers and developers should factor independence study into consideration to meet the educational needs of the gifted in an inclusive system.